2015
DOI: 10.1093/humrep/deu348
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of modern methods of contraception: underlying causes and consequent undesired pregnancies in 35 low- and middle-income countries

Abstract: No external funding was utilized for this report. There are no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 18 publications
3
41
0
2
Order By: Relevance
“…22,25 Nonuse of contraceptions reported by more than twothirds of the study subjects was related to different given reasons, mostly was related to their religious believes followed by fear of side effects and previous experience of method failure and occurrence of pregnancy while using intrauterine device as a contraceptive method. These given reasons were also reported in the study done by Bellizzi et al, 2015 11 who denoted that non-use of contraceptives was mostly reported due to fear of side effects/health concerns, religious opposition to use and underestimated risk of pregnancy.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…22,25 Nonuse of contraceptions reported by more than twothirds of the study subjects was related to different given reasons, mostly was related to their religious believes followed by fear of side effects and previous experience of method failure and occurrence of pregnancy while using intrauterine device as a contraceptive method. These given reasons were also reported in the study done by Bellizzi et al, 2015 11 who denoted that non-use of contraceptives was mostly reported due to fear of side effects/health concerns, religious opposition to use and underestimated risk of pregnancy.…”
Section: Discussionmentioning
confidence: 62%
“…During the first year of contraceptive use, 25-27% women stop using 'calendar' and 'withdrawal' methods due to unintended pregnancy, 15% stop using male condoms, 8% oral contraceptives, 3% injectable, 2% lactational amenorrhea method (LAM) and 0.2% intrauterine devices (IUDs). 10,11 Women, especially those with low education, often switch to less-effective traditional methods of contraception. 12 This has slowed progress in attaining MDG 5.…”
mentioning
confidence: 99%
“…Nonuse of modern contraception typically accounts for the vast majority of unintended pregnancy. Ineffective use of modern contraceptives and underuse of effective, long acting methods accounts for the remainder of unintended pregnancies [15,45,46]. For example, long acting reversible contraceptive methods (LARCs), which have efficacy rates ranging between 94 and 99%, are used by slightly over half of the women who use contraception [15,43].…”
Section: Discussionmentioning
confidence: 99%
“…21 Underuse of modern methods of contraception: underlying causes and consequent undesired pregnancies in 35 low-and middleincome countries. 22…”
Section: Methodsmentioning
confidence: 99%